Sociology in the Czech Republic : Between East and West - Skovajsa, Marek; Balon, Jan (Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2017)
This book offers the first comprehensive overview in English of the history of sociology in what is today the Czech Republic. Divided into six chapters, it traces the institutional development of the discipline from the late 19th century until the present, with an emphasis on the periods most favorable for sociology's institutionalization: the interwar years, the 1960s and the post-1989 era. The narrative places the institutions, persons and ideas that have been central to the discipline into the broader social and political context. Marek Skovajsa and Jan Balon show that sociology in the Czech Republic has been wedded to the dominant political projects of each successive historical period: nation- and state-building until after WWII, the communist experiment in 1948-1989, liberal democratic reconstruction after 1989, and internationalization after 2000. This work will appeal to social scientists and to a general readership interested in Czech culture and society.- Resumé vydavatel
Keywords: dějiny sociologie -- 20.-21. století -- Česko; history of sociology -- 20th - 21st century -- Czechia; elektronické knihy; monografie; electronic books; monographs